Effect of fly ash and coupling agent on the structural, morphological, thermal, and mechanical properties of polyamide 6/acrylonitrile‐butadiene‐styrene blend. Issue 7 (21st April 2021) - Ez‐Zahraoui, Siham; Kassab, Zineb; Ablouh, El‐houssaine; Sehaqui, Houssine; Bouhfid, Rachid; Alami, Jones; El Achaby, Mounir; Qaiss, Abou El Kacem
Abstract: In the present study, coal fly ash (FA) was used as a reinforcement in a thermoplastic matrix blend of polyamide 6/acrylonitrile‐butadiene‐styrene (PA/ABS). In the first part of this work, the as‐received FA (raw FA) was sieved with a 25 μm sieve to obtain FA with particle size less than 25 μm (FA). Then, the physicochemical properties of the raw FA and the FA were determined. Afterwards, FA was used to prepare a masterbatch of 20 wt% FA and 80 wt% PA by twin‐screw extrusion. Using this masterbatch, composites with different FA contents (4.5, 9, 14, and 18.5 wt%), with and without styrene‐(ethylene‐butylene)‐styrene grafted with maleic anhydride (SEBS‐g‐MA) (S‐g‐M), were produced by extrusion, which was followed by injection molding. Subsequently, several characterization techniques were performed to investigate the effect of FA loading and the S‐g‐M coupling agent on the structural, morphological, thermal, and mechanical properties of the developed composites. The results showed that incorporating FA particles in the matrix blend improved the thermal stability and crystallinity, the Young's modulus, the tensile strength, and torsional properties of the composites. In contrast, the addition of S‐g‐M coupling agent to the polymer composites improved the interfacial adhesion between FA particles and the matrix blend. This further enhanced the structural, morphological, thermal, and mechanical properties of the polymer composites. Overall, the use of FA as an inorganic filler improves the thermal and mechanical properties of polymer composites and shows a potential for promising applications.